Desensitising effect of water film on initial decomposition of HMX crystal under nano-cutting conditions by ReaxFF MD simulations. Issue 7 (2nd May 2020) - Cao, Zhimin; Zong, Wenjun; Zhang, Junjie; Xiao, Caiwei; Huang, Jiaohu; Liu, Wei; Wei, Zhiyong; He, Chunlei
ABSTRACT: In this work, the desensitising effect of water film on the diamond cutting of HMX crystal is studied by using reactive force field (ReaxFF) molecular dynamics simulations. The lubrication behavior, reaction kinetics, decomposition products and reaction pathways are particularly studied to reveal the underlying atomistic origins of desensitisation of wet-cutting system. Simulation results show that a film lubrication and its evolutionary behaviour occur at the nano-cutting interface. And forming a complete water-lubricating film is critical for improving thermal stability of the entire cutting system, which is correlated to tool sharpness, HMX properties and water-lubrication method in the actual cutting process. More interestingly, the mechanism of desensitising effect is confirmed to be that the nano-water film inhibits the C–O affinity between diamond tool and HMX, which makes the relatively stable symmetric cleavage of the main ring dominant in the initial decomposition of HMX. Although the type and evolution trend of the decomposition product is similar to that in dry cutting, the degree of decomposition and the severity of HMX are lower in wet-cutting, and the presence of water-lubricating film causes the transition of main dynamic mechanism function of the HMX from the self-catalysed mode into the random nucleation mode.